Cinnamomum camphora var. linaloolifera essential oil on pest control: Its effect on Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) (Research, Society and Development, 2021)
This study evaluated the insecticidal effect of Cinnamomum camphora var. linaloolifera essential oil and its major compound, linalool, on Trialeurodes vaporariorum. Essential oil treatments were applied at 0.5, 1.0, 1.5, and 2.0% v/v on eggs, nymphs, and adult individuals and linalool equivalent concentrations on nymphs of T. vaporariorum. The negative controls water and Tween-80® (0.5% v/v) and a positive control (spiromesifen 0.05% v/v for eggs and nymphs; pymetrozine 0.04% m/v for adults) were also used. The essential oil of C. camphora at 2.0% v/v caused egg mortality of 49.7%; same concentration caused the highest nymph mortality (88.5%). For adults, the essential oil at 2.0% v/v caused the highest mortality (40.0%) after 48 h, not changing from 48 to 72 h. The essential oil and linalool performed similarly relative to the nymphs, whose mortalities have not differed statistically, with exception of the concentrations of 0.5 and 1.0% v/v. Regarding the chemical control, the concentration of 2.0% v/v has had similar mortality for nymphs; for eggs and adults, the essential oil caused lower mortality (49.4 and 40.0%) than the synthetic pesticide (65.0 and 72.0%). The essential oil of C. camphora may be a potential control alternative for T. vaporariorum, especially regarding the Integrated Pest Management (IPM) practices.